2023
DOI: 10.56053/7.2.309
|View full text |Cite
|
Sign up to set email alerts
|

Structural and thermal properties of H6Ta2O17

Abstract: The structural, electronic, mechanical, and thermal properties of H6Ta2O17 are studied using density functional theory. The Helmholtz free energy is computed for various symmetry constraints on the H6Ta2O17 structure during lattice structure optimization and atomic configuration relax- ation. The Helmholtz free energies calculated from Γ-point phonon frequencies demonstrate a pref- erence for slightly lowered symmetry, preferring triclinic symmetry rather than the experimentally determined orthorhombic symmetr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(4 citation statements)
references
References 10 publications
0
4
0
Order By: Relevance
“…In general, Schiff bases or metal complexes exert their effects by inhibiting enzymes, enhancing lipophilicity, interacting with biomolecules, arresting the cell cycle, and altering cell membrane functions [ 72 ]. For example, many metal complexes of the quinolone group of some antibiotics are reported to possess enhanced activity compared to antibiotics alone [ 73 ] and suggest potential avenues for further improvement [ 74 , 75 , 76 , 77 , 78 , 79 , 80 ].…”
Section: Resultsmentioning
confidence: 99%
“…In general, Schiff bases or metal complexes exert their effects by inhibiting enzymes, enhancing lipophilicity, interacting with biomolecules, arresting the cell cycle, and altering cell membrane functions [ 72 ]. For example, many metal complexes of the quinolone group of some antibiotics are reported to possess enhanced activity compared to antibiotics alone [ 73 ] and suggest potential avenues for further improvement [ 74 , 75 , 76 , 77 , 78 , 79 , 80 ].…”
Section: Resultsmentioning
confidence: 99%
“…For KZnP, the curve shows multiple peaks of conductivity highest being 8453.14 ohm −1 cm −1 at 3.225 eV, then it decreases presenting several small peaks until reaching a minimum value, 663.30 ohm −1 cm −1 , then the curve goes back up reaching a peak of 5804.91 ohm −1 cm −1 that is relatively smaller to highest one, then it decreases gradually until stabilizing towards 307.80 ohm −1 cm −1 . To highlight the importance of various factors in achieving optoelectronic studies, it has suggested potential avenues for further improvement [47][48][49][50][51][52][53].…”
Section: Conductivitymentioning
confidence: 99%
“…The exchange correlation energy/potential functionals that are commonly used include the local spin density approximation (LSDA), the LSDA + USIC, the spin-Perdew–Burke–Ernzerhof generalized gradient approximation (PBE–GGA), the PBE–GGA + USIC, the PBESol, and the PBESol + U. The ternary arsenide zintl phases have strong electrical properties, mainly contributed by the As-p states calculated from the electronic structure combined with Boltzmann theory for transport phenomena using the pseudo-potential plane-wave method with GGA–PBEsol, which accurately predicted the equilibrium lattice and positional parameters. , Research on laves-phase PrFe 2 and PrRu 2 compounds exhibits superconductivity with critical temperatures of 550 and 580 K, respectively, calculated by using the GGA–PBESol + U approximation to address the f states of Pr atoms and the d states of Fe and Ru atoms . The lead halide double perovskites have demonstrated potential as a material for thermal conductivity at both high and low temperatures.…”
Section: Introductionmentioning
confidence: 99%